Electronic and traditional savings accounts in colombia: A spatial agglomeration model (2018)
The purpose of this article is to apply a multivariate spatial statistics technique: cluster analysis or spatial agglomeration, in order to classify departments into groups based on behavior in the number of active, inactive electronic savings accounts and savings traditional active accounts, with database available as of September 2017 in the bank of Colombia. The selection of this type of accounts was due to the fact that the financial product with the highest penetration in the Colombian population in September 2017, continued to be the savings account; 73.5% of the population had this financial product. However, this percentage is far from the target of 84% proposed in the National Development Plan. The findings show that the departments where electronic accounts are most used are Cauca, Bogotá, Meta, Casanare, Arauca, Vichada, Huila, Amazonas, Guainía, Vaupés, Caldas, Chocó, Sucre, La Guajira, César, Norte de Santander, however, the levels of penetration of this type of product are very low yet in the Colombian territory.